HUBUNGAN PANJANG TUNGKAI DAN KEKUATAN OTOT TUNGKAI TERHADAP KEMAMPUAN SHOOTING PADA PERMAINAN SEPAKBOLA SMA NEGERI 2 KOTABARU - Jusran S (CENDEKIA: JURNAL ILMIAH PENDIDIKAN, 2017)
This research is a descriptive research type. This study aims to determine: (1) To determine whether there is a relationship between the length of the leg with shooting ability in football game SMAN 2 Kotabaru. (2) To find out if there is a relationship between leg muscle strength with shooting ability in football game of SMAN 2 Kotabaru football game. (3) To find out whether there is a relationship between leg length and leg muscle strength with shooting ability in football game SMAN 2 Kotabaru. The population is Student MAN Kotabaru. The sample used is a student of SMAN 2 Kotabaru 30 people. The technique of determining the sample is by random selection by drawing method (Simple Random Sampling). Data analysis technique used inferential descriptive analysis analysis through SPSS 20 program at significant level Î± 0,05. The results showed that; (1) the relationship between leg length and shooting abilities in the SMAN 2 Kotabaru football game, with a value of Ï of 0.544 (0.01 <0.05); (2) There is a significant relationship between leg muscle strength and shooting ability in football soccer game SMAN 2 Kotabaru, with value Ï of 0.353 (0.028 <0.05); (3) There is a relationship between leg length and leg muscle strength with shooting ability in football game SMAN 2 Kotabaru, with Rhitung value of 0,547 (0,008 <0,05); and the Fcount of 5.778 Keywords: Limb Length and Muscle Limb Strength With Shooting Capability In Soccer Game